(3GdbGfhfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3MSf Hf jhSa Hf YhGV GdfMhi s)
(3ChdgG (B:s
(3GdebGdI GdChdi ai GdMejGJ GdMei MQGQI ZQjHI JTJYd ai hJfHK efg eJhSW GdQhM hGdOe hGdYQhb hLejY GdHOf ef bSe GdMei Edi bSejf s
(3BNQgG (B:s
(3GdbhGfhSGf (B: (3KdGK ChGb, KeGfjI ChKhdh , CQHYI hYTQhf bjQGWkG s
(3GdfSNI ebGHdIs
(3hcJHJ YfGhjfgG HGdMeQIs
(3JTJed Ydi GdebGdI GdChdi ai GdMejGJ hJfJgi HGdebGdI GdKGefI ai OGA GdKYdHs
(3fSNI SGHYI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdWHs